TECHNOLIBERAL PARTICIPATION: BLACK LIVES MATTER AND INSTAGRAM SLIDESHOWS - Salzano, Matthew (AoIR Selected Papers of Internet Research, 2021)
After the murder of George Floyd in May 2020, Black Lives Matter protests surged around the globe. Amid COVID-19, activism on social media flourished. On Instagram, use of the ten-image carousel as an informative slideshow akin to a PowerPoint presentation gained significant attention: The New York Times highlighted their “effort to democratize access to information." In this paper, I rhetorically analyze case studies to illustrate how Instagram slideshows facilitated deliberation about participation. I argue that these posts reveal a tension in platformed digital activism: as digital templates broaden access to participation, technoliberal ideology constrains activist judgment.